Kilka uwag o tworzeniu tekstu przez Benedykta XVI - Ożóg, Kazimierz (Słowo. Studia językoznawcze, 2013)
Based on the three volumes of “Jesus of Nazareth”, the article is an attempt to analyze various methods employed by Benedict XVI in creating texts. Pope Benedict’s writing style may be described as both clear and spirited, a disciplined approach to writing is also visible. Frequently, figures of speech (such as the road is as a metaphor) and metatextual formulas are applied in his texts in order to facilitate their reception.